Lack of evidence of rotavirus‐dependent molecular mimicry as a trigger of coeliac disease. (29th September 2016) - Ziberna, F.; De Lorenzo, G.; Schiavon, V.; Arnoldi, F.; Quaglia, S.; De Leo, L.; Vatta, S.; Martelossi, S.; Burrone, O. R.; Ventura, A.; Not, T.
Summary: New data suggest the involvement of rotavirus (RV) in triggering autoimmunity in coeliac disease (CD) by molecular mimicry between the human‐transglutaminase protein and the dodecapeptide (260‐271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured anti‐pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy‐proven CD patients and 46 patients with potential CD; 32 children with other gastrointestinal diseases; 107 no‐CD children and 107 blood donors. Using enzyme‐linked immunosorbent assay (ELISA) assay, we measured immunoglobulin (Ig)A–IgG antibodies against the synthetic peptides pVP7, the human transglutaminase‐derived peptide (476–487 aa) which shows a homology with VP7 protein and a control peptide. The triple‐layered RV particles (TLPs) containing the VP7 protein and the double‐layered RV‐particles (DLPs) lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV‐TLPs was positive in 22 of 118 (18%) CD patients and in both paediatric (17 of 107, 16%) and adult (29 of 107, 27%) control groups, without showing a statistically significant difference among them ( P  = 0·6, P  = 0·1). Biopsy‐proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34 of 118, 29% CD patients; 66 of 107, 62% adult controls) and control synthetic peptides (35 of 118, 30% CD patients; 56 of 107, 52% adult controls), suggesting a non‐specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. Abstract : New data suggest the involvement of rotavirus in triggering autoimmunity in celiac disease by molecular mimicry between the human tissue type 2 transglutaminase protein and a part of the rotavirus related VP7 protein. The strength of our study lies in its having monitored immunological reactivity to native and well‐characterized viral antigens in the sera of both celiac patients and controls at a young age, very close to a rotavirus infection, without finding any difference in the two study groups. The data we have gathered fail to support the hypothesis of celiac disease‐autoimmunity induced by mechanisms related to molecular mimicry between the rotavirus‐VP7‐peptide and the human tissue type 2 transglutaminase protein.